Oncofetal proteins regulate proliferation and differentiation in placental cells - West, Rachel Claire, author; Winger, Quinton, advisor; Bouma, Gerrit, advisor; Anthony, Russ, committee member; Hamilton, Karyn, committee member (Colorado State University. Libraries, 2018)
The chromatin associated transcription factor HMGA2 is a downstream target of let-7 miRNAs and binds to chromatin to regulate gene expression, inducing rapid cell proliferation during embryogenesis. Inhibition of let-7 miRNAs by RNA binding proteins LIN28A and LIN28B is necessary during early embryogenesis to ensure stable expression of HMGA2 and proper cell proliferation. In addition to LIN28, HMGA2 is regulated by a BRCA1/ZNF350/CtIP repressor complex. In normal tissues, the BRCA1/ZNF350/CtIP complex binds to the HMGA2 promoter to prevent transcription. However, in many cancers the oncomiR miR-182 targets BRCA1, preventing BRCA1 translation and allowing for increased HMGA2. Little is known about the regulation of HMGA2 during early placental development therefore we hypothesized that both LIN28 and BRCA1 can regulate HMGA2 in placental cells. Using siRNA and CRISPR gene editing techniques, we found that knockdowns of both LIN28A and LIN28B increase HMGA2 levels in ACH-3P cells. These cells also demonstrated deficiencies in cell differentiation towards the syncytiotrophoblast, secreting higher amounts of hCG and displaying upregulated ERVW-1. Additionally, we found that a knockout of both LIN28A and LIN28B caused a significant increase of miR-182 and a decrease in BRCA1 which allows HMGA2 mRNA levels to increase and protein levels to remain the same. Using chromatin immunoprecipitation, we saw binding of the BRCA1 repressor complex to HMGA2. We also saw a decrease in binding to HMGA2's promoter in the LIN28A/B knockout cells. These findings suggest a novel role for BRCA1 during early human placental development. To test this hypothesis, we used CRISPR-Cas9 gene editing to knockout BRCA1 in the Swan71 cell line as the Swan71 cells had significantly higher BRCA1 levels compared to ACH-3P cells. HMGA2 mRNA and protein was significantly increased in the BRCA1 KO cells compared to control cells. Chromatin immunoprecipitation was used with an antibody for ZNF350 and PCR was run using primers for the promoter region for HMGA2. We saw a loss of BRCA1 repressor complex binding to HMGA2 in the knockout cells compared to our control cells, leading us to conclude that increased HMGA2 was due to decreased binding of the BRCA1 repressor complex. Additionally, we tested levels of apoptosis in our cells. After serum starving cells for 16 hours, we found that Caspase 3 and 7 levels were significantly higher in our BRCA1 KO cells compared to controls. This data suggests that BRCA1 is an important factor in the regulation of the oncofetal protein HMGA2 and promotes cell survival in human placental cells.
Keywords: gene editing; placental insufficiency; reproductive physiology; placenta; BRCA1; preeclampsia